PENGELOMPOKAN DATA PENDUDUK MISKIN DI SUMATERA UTARA MENGGUNAKAN K-MEANS - Ayu Safitri; Rizki Rahmawati; Sri Ayu Wandira (LPPM STMIK Royal Kisaran, 2024)
Abstract: The government has made many efforts to eradicate poverty in society by implementing programs such as pro-poor, basic food assistance and cash assistance which are useful for achieving the standards of a prosperous society. The results of data processing are useful in future decision making. Considering the large amount of public data, finding out poor people is not an easy thing for the government to do, as is the case in North Sumatra. This research uses the K-Means Clustering (Multidimensional) method, making it easier to see patterns and structures in data that are difficult to see in the original representation. The application of the K-Means Clustering (Multidimensional) algorithm produces 3 clusters with a silhouette_score value of 33, namely cluster 0 with a high level of population poverty of 1, cluster 1 with a moderate level of population poverty of 4 and cluster 2 with a low level of population poverty as many as 28. Keywords: Resident; Poor; Data Mining; K-Means Abstrak: Banyak upaya yang dilakukan pemerintah untuk menghapus kemiskinan pada masyarakat dengan cara melakukan program seperti pro-poor, bantuan sembako maupun bantuan uang tunai yang berguna untuk mencapai standar masyarakat sejahtera. Hasil pengolahan data tersebut berguna dalam pengambilan keputusan kedepannya. Mengingat banyaknya data masyarakat, maka untuk mengetahui masyarakat miskin bukanlah hal mudah yang dilakukan oleh pemerintah, sama halnya di Sumatera Utara. Penelitian ini menggunakan metode K-Means Clustering (Multidimensi) memudahkan untuk melihat pola dan struktur dalam data yang sulit dilihat dalam representasi aslinya. Penerapan algoritma K-Means Clustering (Multidimensi) menghasilkan 3 cluster, yaitu dengan cluster 0 dengan tingat kemiskinan penduduk yang tinggi sebanyak 1, cluster 1 dengan tingat kemiskinan penduduk yang sedang sebanyak 4 dan cluster 2 dengan tingkat kemiskinan penduduk yang rendah sebanyak 28. Kata kunci: Penduduk; Miskin; Multidimensi; Data Mining; K-Means